LAUNCHING DAN SOSIALISASI ELEKTRONIK SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (E-SAKIP) DI KABUPATEN PRINGSEWU - Agustinus Eko Setiawan; Ratnasari Ratnasari; Defy Gustianing; Fahlul Rizki; Sunarmi Sunarmi; Zulkifli Zulkifli (LPPM Universitas Bina Bangsa, 2023)
The realization of good governance and accountability is the expectation of all parties. Regarding these expectations, it is necessary to develop and implement an accountability system that is appropriate, clear, measurable, and accurate. In realizing this effort, the Regency Government of Pringsewu in collaboration with the Aisyah University of Pringsewu created an electronic application for Government Agency Performance Accountability Systems (E-Sakip), namely an application for reporting performance measurement results to Government Agencies. The E-Sakip launching and outreach activities will be held on Monday, November 28th, 2022 at the Main Hall of the Regency Government of Pringsewu. The method used in this socialization is an introduction or lecturing method, then carrying out simulations or demonstrations which are attended by 80 participants consisting of the Head of the Planning Subdivision and Functional Officers. The material presented included creating user accounts for the application, account creation and user access rights for the LAKIP reporting unit, filling out the LAKIP document components, how to upload LAKIP documents, and how to change the password on the user account. The result of this community service activity is that the E-Sakip application can be implemented in the Regency Government of Pringsewu and it provides knowledge to participants who represent each Government Agency in the Pringsewu Region regarding the use of the E-Sakip application which can assist the Government Agencies in Digital Performance Accountability Reports